Manejo del google drive y aprendizaje significativo en estudiantes de seminario de investigación III educación inicial facultad de ciencias de la educación y humanidades Universidad Nacional de la Amazonía Peruana, Iquitos 2020-2021 - Shuña Bonifaz, Valeria Polita (2023)
The objective of the research was to determine the relationship between the management of the google drive and significant learning in students of the Seminar on Educational Research III Initial Education of the Faculty of Educational Sciences and Humanities at the National University of the Peruvian Amazon in Iquitos in the 2020-2021 period. In the methodology, the type of relational research was adopted, through a field, cross-sectional, and bivariate design. The population was composed of 45 students of Initial Education and the sample was census, the same students. The survey was the data collection technique and questionnaires as instruments, which were validated through expert judgment. The conclusion of the research is that the values of the Chi-square test = 23.535 and p = 0.000 and Kendall's Tau-b coefficient = 0.550, show that the relationship is direct and strong between the variables, so there is a significant relationship between the management of google drive and significant learning in students of the Seminar on Educational Research III Initial Education of the Faculty of Educational Sciences and Humanities at the National University of the Peruvian Amazon, also confirming the hypothesis proposed for the investigation.